Prognostic value of circulating tumour cells in limited-stage small-cell lung cancer: analysis of the concurrent once-daily versus twice-daily radiotherapy (CONVERT) randomised controlled trial. (24th April 2019) - Tay, R Y; Fernández-Gutiérrez, F; Foy, V; Burns, K; Pierce, J; Morris, K; Priest, L; Tugwood, J; Ashcroft, L; Lindsay, C R; Faivre-Finn, C; Dive, C; et al.
Abstract: Background: The clinical significance of circulating tumour cells (CTCs) in limited-stage small-cell lung cancer (LS-SCLC) is not well defined. We report a planned exploratory analysis of the prevalence and prognostic value of CTCs in LS-SCLC patients enrolled within the phase III randomised CONVERT (concurrent once-daily versus twice-daily chemoradiotherapy) trial. Patients and methods: Baseline blood samples were enumerated for CTCs using CellSearch in 75 patients with LS-SCLC who were enrolled in the CONVERT trial and randomised between twice- and once-daily concurrent chemoradiation. Standard statistical methods were used for correlations of CTCs with clinical factors. Log-rank test and Cox regression analyses were applied to establish the associations of 2, 15 and 50 CTC thresholds with progression-free survival (PFS) and overall survival (OS). An optimal CTC count threshold for LS-SCLC was established. Results: CTCs were detected in 60% (45/75) of patients (range 0–3750). CTC count thresholds of 2, 15 and 50 CTCs all significantly correlate with PFS and OS. An optimal CTC count threshold in LS-SCLC was established at 15 CTCs, defining 'favourable' and 'unfavourable' prognostic risk groups. The median OS in <15 versus ≥15 CTCs was 26.7 versus 5.9 m ( P = 0.001). The presence of ≥15 CTCs at baseline independently predicted ≤1 year survival in 70% and ≤2 years survival in 100% of patients. Conclusion: We report the prognostic value of baseline CTC count in an exclusive LS-SCLC population at thresholds of 2, 15 and 50 CTCs. Specific to LS-SCLC, ≥15 CTCs was associated with worse PFS and OS independent of all other factors and predicted ≤2 years survival. These results may improve disease stratification in future clinical trial designs and aid clinical decision making. Trial registration: ClinicalTrials.gov identifier: NCT00433563.